We own the future : democratic Socialism-American style - Aronoff, Kate; Kazin, Michael, 1948-; Dreier, Peter, 1948- (New York : The New Press, 2020)
"A stunningly original and timely collection that makes the case for "socialism, American style""--
Includes bibliographical references.
Keywords: Socialism -- United States -- History; Socialismo -- Estados Unidos -- Historia; Democracy -- United States -- History; Democracia -- Estados Unidos -- Historia